Microenvironmental Regulation of Macrophage Transcriptomic and Metabolomic Profiles in Pulmonary Hypertension - Li, Min; Riddle, Suzette; Kumar, Sushil; Poczobutt, Joanna; McKeon, B. Alexandre; Frid, Maria G.; Ostaff, Maureen; Reisz, Julie A.; Nemkov, Travis; Fini, Mehdi A.; Laux, Aya; Hu, Cheng-Jun; et al. (Frontiers in Immunology, 2021)
The recruitment and subsequent polarization of inflammatory monocytes/macrophages in the perivascular regions of pulmonary arteries is a key feature of pulmonary hypertension (PH). However, the mechanisms driving macrophage polarization within the adventitial microenvironment during PH progression remain unclear. We previously established that reciprocal interactions between fibroblasts and macrophages are essential in driving the activated phenotype of both cell types although the signals involved in these interactions remain undefined. We sought to test the hypothesis that adventitial fibroblasts produce a complex array of metabolites and proteins that coordinately direct metabolomic and transcriptomic re-programming of naïve macrophages to recapitulate the pathophysiologic phenotype observed in PH. Media conditioned by pulmonary artery adventitial fibroblasts isolated from pulmonary hypertensive (PH-CM) or age-matched control (CO-CM) calves were used to activate bone marrow derived macrophages. RNA-Seq and mass spectrometry-based metabolomics analyses were performed. Fibroblast conditioned medium from patients with idiopathic pulmonary arterial hypertension or controls were used to validate transcriptional findings. The microenvironment was targeted in vitro using a fibroblast-macrophage co-culture system and in vivo in a mouse model of hypoxia-induced PH. Both CO-CM and PH-CM actively, yet distinctly regulated macrophage transcriptomic and metabolomic profiles. Network integration revealed coordinated rewiring of pro-inflammatory and pro-remodeling gene regulation in concert with altered mitochondrial and intermediary metabolism in response to PH-CM. Pro-inflammation and metabolism are key regulators of macrophage phenotype in vitro, and are closely related to in vivo flow sorted lung interstitial/perivascular macrophages from hypoxic mice. Metabolic changes are accompanied by increased free NADH levels and increased expression of a metabolic sensor and transcriptional repressor, C-terminal binding protein 1 (CtBP1), a mechanism shared with adventitial PH-fibroblasts. Targeting the microenvironment created by both cell types with the CtBP1 inhibitor MTOB, inhibited macrophage pro-inflammatory and metabolic re-programming both in vitro and in vivo. In conclusion, coordinated transcriptional and metabolic reprogramming is a critical mechanism regulating macrophage polarization in response to the complex adventitial microenvironment in PH. Targeting the adventitial microenvironment can return activated macrophages toward quiescence and attenuate pathological remodeling that drives PH progression.